OPTIMIZATION OF WEB-BASED DATA FOR MUHAMMADIYAH AL-QUR'AN EDUCATION PARKS IN SIDOARJO REGENCY USING THE R&D AND WATERFALL METHODS - Farihah, Anis; Rahmawati, Yunianita (PT ANTIS INTERNATIONAL PUBLISHER, 2026)
Objective: This research aims to develop a web-based information system for optimizing data at Muhammadiyah Quran Education Parks (TPQ) in Sidoarjo Regency. The background of this research is based on the problem of managing TPQ institutional data, which is still manual, separate, and difficult to access in an integrated manner, making monitoring, validation, and reporting difficult. Method: The research method uses a Research and Development (R&D) approach with the Waterfall development model. Results: The research results show that the information system built is able to integrate data on students, teachers, curriculum, activities, and institutional administration online. This system simplifies data management, improves reporting efficiency, and supports transparency and accountability in the guidance of TPQ by the Muhammadiyah Tabligh Council of Sidoarjo Regency. Novelty: The novelty of this research lies in the development of a web-based information system that integrates multiple aspects of TPQ data management, providing a solution to the challenges of manual and separate data handling, and improving overall efficiency and accountability in TPQ administration.